2017
DOI: 10.1111/cpr.12416
|View full text |Cite
|
Sign up to set email alerts
|

LINC00473 antagonizes the tumour suppressor miR‐195 to mediate the pathogenesis of Wilms tumour via IKKα

Abstract: Objectives: Although dramatic improvements of overall survival has achieved in patients with favourable histology Wilms tumour, disease recurrence is still the main cause of cancer-related death in childhood. Long non-coding RNAs (lncRNAs) as oncogenes or tumour suppressors are dysregulated during carcinogenesis. However, the role of lncRNAs in the pathogenesis of Wilms tumour is unknown. Here, an lncRNA LINC00473 signature that functioned as oncogene was identified in Wilms tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 28 publications
3
75
0
Order By: Relevance
“…7 Moreover, LINC00473, as an oncogene, is upregulated to participate in the progression of WT via miR-195/IKKα. 8 Wang et al have demonstrated that miR-194-5p inhibits cell migration and invasion via directly targeting E2F3 in bladder cancer. 9 MiR-194-5p was reported to inhibit EMT by reducing E-cadherin and inhibited cell migration, invasion, and metastasis in gastric cancer, metrocarcinoma, and liver cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…7 Moreover, LINC00473, as an oncogene, is upregulated to participate in the progression of WT via miR-195/IKKα. 8 Wang et al have demonstrated that miR-194-5p inhibits cell migration and invasion via directly targeting E2F3 in bladder cancer. 9 MiR-194-5p was reported to inhibit EMT by reducing E-cadherin and inhibited cell migration, invasion, and metastasis in gastric cancer, metrocarcinoma, and liver cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…CREB-induced LINC00473 acts as an oncogene in LKB1-inactivation NSCLC, CRTC1-MAML2 fusionpositive MEC, and several other cancer cells [18,19,[22][23][24]. In this work, we found that LINC00473 functioned as an oncogene in MCF-7 cells as well and discovered dual regulatory mechanisms of LINC00473 on CCND1 transcriptional control.…”
Section: Discussionmentioning
confidence: 52%
“…Increasing studies have certified that miRNAs are promising biomarkers for Wilms’ tumor treatment. For example, miR‐195 functioned as a tumor suppressor to regulate the progression of Wilms’ tumor by targeting IKKα (Zhu et al, 2018). miRNA‐572 facilitates metastasis and EMT process in Wilms’ tumor via targeting CDH1 (Zhang, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%